2015
DOI: 10.1111/1462-2920.13036
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gaps on the viral photosystem‐IpsaDCAB gene organization

Abstract: SummaryMarine photosynthesis is largely driven by cyanobacteria, namely Synechococcus and Prochlorococcus. Genes encoding for photosystem (PS) I and II reaction centre proteins are found in cyanophages and are believed to increase their fitness. Two viral PSI gene arrangements are known, psaJF→C→A→B→K→E→D and psaD→C→A→B. The shared genes between these gene cassettes and their encoded proteins are distinguished by %G + C and protein sequence respectively. The data on the psaD→C→A→B gene organization were report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
2
2
0
1
Order By: Relevance
“…The observed links between GroEL phylogeny, chaperonin gene order and associations with nearby genes demonstrated that large subunit chaperonins are a defining feature of certain virioplankton populations. Similar to findings for DNA polymerase A ( Schmidt et al , 2014 ), ribonucleotide reductase ( Dwivedi et al , 2013 ; Sakowski et al , 2014 ) and photosystem genes ( Mann et al , 2003 ; Sullivan et al , 2006 ; Roitman et al , 2015 ), important biological and ecological characteristics may be linked with the type and organization of chaperonin genes a virus carries. Given the common observation of chaperonin genes within viromes, it is surprising that so few known viruses carry chaperonin genes.…”
Section: Discussionsupporting
confidence: 61%
“…The observed links between GroEL phylogeny, chaperonin gene order and associations with nearby genes demonstrated that large subunit chaperonins are a defining feature of certain virioplankton populations. Similar to findings for DNA polymerase A ( Schmidt et al , 2014 ), ribonucleotide reductase ( Dwivedi et al , 2013 ; Sakowski et al , 2014 ) and photosystem genes ( Mann et al , 2003 ; Sullivan et al , 2006 ; Roitman et al , 2015 ), important biological and ecological characteristics may be linked with the type and organization of chaperonin genes a virus carries. Given the common observation of chaperonin genes within viromes, it is surprising that so few known viruses carry chaperonin genes.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, vFAD-IIs are present only in the Southern Pacific and Southern Atlantic Oceans, as well as in the Indian Ocean ( Figure 3a , purple dots). Interestingly, the geographical distribution and abundance of vFAD-II resembles the data found for uncultured phages carrying the vPSI-4 gene cassette ( Roitman et al , 2015 ), which is also found in the 94 kbp contig ( Figure 1 ). To estimate the vFAD relative abundance, we mapped the raw reads from the Tara Ocean metagenomes corresponding to bacterial, giant viruses and viral fractions to the viral desC genes.…”
Section: Resultssupporting
confidence: 67%
“…Errors in the assembly were corrected using two read-mapping-based in-house tools as described elsewhere ( Philosof et al , 2017 ). Viral psaD sequences obtained in a previous study of vPSI-4 genes ( Roitman et al , 2015 ) were used as query to recruit scaffolds in the reassembled Tara Ocean data set using TBLASTX ( Altschul et al , 1990 ; Camacho et al , 2009 ) with the default parameters. One of the identified scaffolds, SAMEA2621085 (station 70, depth 5 m, 0–0.22 filter), contains the four genes of vPSI-4 ( psaD , C , A and B ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Les bactériophages sans gaine contractile sont les plus abondants [2]. 1600 nouveaux génomes viraux ont été rassemblés [3] à partir de diverses populations [4], et des connaissances plus spécifiques sur divers processus biologiques ont été acquises [3,[5][6][7]. Les grands virus à ADN des eucaryotes sont abondants et diversifiés [8][9][10], et notre laboratoire a récemment montré que la résistance aux prasinovirus peut être acquise et provoque des changements importants dans le génome de l'algue phytoplanctonique Ostreococcus tari [11].…”
Section: C3 Tara Océans Et Virus Nigel Grimsley Biologie Intégrative unclassified